Distribution of Spodoptera frugiperda (Lepidoptera: Noctuidae) strains and their association with different landscape structures in Bali, Indonesia - Monica, Dheya Cintya; Kusumah , Yayi Munara; Winasa , I Wayan Winasa (Universitas Lampung, 2026)
Spodoptera frugiperda, commonly known as the Fall Armyworm (FAW), is an invasive pest originating from the Americas that poses a serious threat to maize production in Bali, with potential crop losses reaching up to 50%. To monitor its genetic distribution, this study employed molecular identification using the mitochondrial cytochrome oxidase subunit I (mtCOI) and triosephosphate isomerase (Tpi) gene markers. The research aimed to identify FAW strains present in Bali and to assess their distribution across different landscape structures. The study consisted of four main stages: (1) sample and coordinate collection, (2) DNA extraction, amplification, and sequencing, (3) molecular data analysis, and (4) spatial analysis using QGIS, Google Earth Pro, and RStudio 4.3.1 with a generalized linear model (GLM). showed that the COI-R/Tpi-C strain was dominant in the central (Badung and Tabanan) and eastern (Klungkung) regions of Bali, whereas the COI-C/Tpi-C strain was found in the northern (Buleleng), southern (Denpasar), and western (Jembrana) regions. FAW haplotypes were relatively evenly distributed across all sampling locations. No significant association was detected between FAW strain distribution and landscape structure, leaving unclear which vegetation types act as ecological corridors or barriers. The low strain and haplotype diversity observed across both gene markers suggests that genetic variation is largely confined within, rather than between, regions, resulting in a relatively uniform distribution of FAW haplotypes across Indonesia, including Bali.